Bioassay guided isolation of antibacterial compounds from Andrographis paniculata - Sule, Abubakar; Ahmed, Qamar Uddin; Abd. Samah, Othman; Omar, Muhammad Nor; Mohd Hassan, Norazian; Mohd Kamal, Laina Zarisa; Yarmo, Mohd Ambar (Science Publications, 2011)
Problem statement: Chronic disease-causing bacteria of medical importance have developed resistance to antibiotics, hence, necessitating distinct and constant need for safe and efficient therapeutic agents. Plants are considered potent candidate for this aim. A way out of reducing antibiotic resistance and adverse effects on host is the employment of antibiotic resistance inhibitors of plant origin. Approach: About 5 kg pulverized Andrographis paniculata whole plant was macerated with MeOH at room temperature to get 305 g freeze dried MeOH extract. The bioautography of MeOH extract using Staphylococcus aureus and Proteus mirabilis as indicator organisms revealed the presence of two potent antibacterial compounds. MeOH extract was further fractionated and purified by silica gel column chromatography which led to the isolation of a diterpene lactone and an entlabdane diterpene glycoside upon crystallization with absolute ethanol. Results: Two antibacterial compounds viz., 3-O-â-D-glucosyl-14-deoxyandrographolide and 14-deoxyandrographolide were successfully isolated and characterized. Their structures were exclusively elucidated through spectroscopic methods (UV, IR, 1H- and 13C NMR). Conclusion: A. paniculata possesses antibacterial activity and could be potential source of a new class of antibiotics that might be useful for infectious disease chemotherapy and contro